Competencies for effective leadership : a framework for assessment, education, and research - Gigliotti, Ralph A. (Emerald Publishing Limited, 2019)
What makes a leader? In this critical time of change for leaders, it has become increasingly important to understand the competencies associated with leadership. This essential book explores the ways in which Brent Ruben's Leadership Competency Scorecard can be used within an organizational setting.